2012
DOI: 10.1074/jbc.m112.386458
|View full text |Cite
|
Sign up to set email alerts
|

The Archaeal Proteasome Is Regulated by a Network of AAA ATPases

Abstract: Background: The AAA ATPases of the PAN/Rpt1–6 group regulate access of substrates to the 20S proteasome.Results: Two groups of AAA proteins, CDC48 and AMA, function as novel proteasomal ATPases in archaea.Conclusion: This network of regulatory ATPases increases the capacity of proteasomal protein degradation in archaea.Significance: Diversification at the level of the regulatory ATPase provides a contrast to the fully differentiated 26S proteasome of eukaryotes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
46
0

Year Published

2013
2013
2019
2019

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 43 publications
(51 citation statements)
references
References 54 publications
(68 reference statements)
0
46
0
Order By: Relevance
“…The residues for accommodating the C-terminal tail of HiHslU, Phe 54 , Phe 57 , and Gln 114n are replaced with smaller or shorter residues (i.e. Ile 54 , Met 57 , and Thr 114n , respectively) in TbHslV. This explains why EcHslU and TbHslU1 are not able to activate TbHslV, most probably due to the weak binding.…”
Section: Discussionmentioning
confidence: 95%
See 1 more Smart Citation
“…The residues for accommodating the C-terminal tail of HiHslU, Phe 54 , Phe 57 , and Gln 114n are replaced with smaller or shorter residues (i.e. Ile 54 , Met 57 , and Thr 114n , respectively) in TbHslV. This explains why EcHslU and TbHslU1 are not able to activate TbHslV, most probably due to the weak binding.…”
Section: Discussionmentioning
confidence: 95%
“…The HslVU complex in prokaryotes and archaea possesses a simple architecture consisting of a homododecameric HslV and two homohexameric HslUs, but archaeal and eukaryotic proteasomes display a more complicated configuration. In archaea, several proteasomal ATPases, including proteasome-activating nucleotidase and CDC48, constitute a regulatory network (57), and in eukaryotes, heterooligomeric ATPases function within the base of the 19 S regulatory particle. In contrast to prokaryotic and archaeal HslUs, the eukaryotic HslUs from T. brucei and Leishmania donovani possess two HslU homologs, HslU1 and HslU2 (28,29); this suggests several possible configurations of the T. brucei HslVU complex from a structural point of view: 1) two independent TbHslVU1 and TbHslVU2 complexes; 2) TbHslV asymmetrically capped with hexameric rings of TbHslU1 and TbHslU2, and 3) TbHslV complexed with the hetero-oligomeric TbHslU ring consisting of both TbHslU1 and TbHslU2.…”
Section: Discussionmentioning
confidence: 99%
“…Both D1 and D2 are homologous to the single AAA+ modules of PAN and Rpt1-6 (1,16). Biochemical studies have shown that VAT unfolds globular proteins and interacts directly with the 20S core particle (CP) of the proteasome, leading to enhanced proteolytic activity for both folded and unfolded protein substrates (18)(19)(20)(21). In eukaryotes, the enzymes Cdc48 and p97/VCP, which are homologous to VAT, play essential roles in a large number of cellular functions, including transcriptional and metabolic regulation, cell cycle progression, membrane fusion, apoptosis, and protein degradation (22).…”
mentioning
confidence: 99%
“…2A). Recent studies on the archaeal p97/VCP homolog Cdc48 and the 20S proteasome suggested that direct and functional interactions between Cdc48 and the 20S proteasome can take place in vitro, which align the central cavities of these two ring-shaped complexes, forming a continuous conduit through which substrates are transferred from Cdc48 to the 20S proteasome for degradation Sauer, 2012, 2013;Forouzan et al, 2012). Such interactions, if they exist in eukaryotes, would provide a simple coupling mechanism that links retrotranslocation to degradation.…”
Section: P97/vcp: a Multifaceted Cellular Enzymementioning
confidence: 99%